2010
DOI: 10.2144/000113363
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the relative amount of mouse and human DNA in cancer xenografts using species-specific variation in gene length

Abstract: Human cancer cell lines and xenografts are valuable samples for whole-genome sequencing of human cancer. Tumors can be maintained by serial xenografting in athymic (nude) or severe combined immunodeficient (SCID) mice. In the current study, we developed a molecular assay to quantify the relative contributions of human and mouse in mixed DNA samples. The assay was designed based on deletion/insertion variation between human and mouse genomes. The percentage of mouse DNA was calculated according to the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…DNA/RNA from xenografts is always contaminated, and although an assay has been published (10) to quantify the proportion of human/mouse DNA in the samples from pancreatic cancer, a generalized method is still lacking. Various studies have reported the need to preprocess xenograft data before performing downstream analysis (9,13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA/RNA from xenografts is always contaminated, and although an assay has been published (10) to quantify the proportion of human/mouse DNA in the samples from pancreatic cancer, a generalized method is still lacking. Various studies have reported the need to preprocess xenograft data before performing downstream analysis (9,13).…”
Section: Methodsmentioning
confidence: 99%
“…Although efforts can be made to mitigate these effects experimentally, high levels of infiltrating stromal cells often render this impractical. Consequently, levels of contamination as high as 73% have been observed in pancreatic cancer patient-derived xenograft (PDX) models (10), and data are often variable (11). Instead, studies have typically addressed readheterogeneity in silico (9,12).…”
Section: Introductionmentioning
confidence: 99%
“…The error rates and read length challenges also place limitations on species differentiation. Many experimental systems and samples used for drug discovery contain sequences from multiple species, such as human cancer xenografts in mouse and bacterial or other cell types in human specimens [22]. SGST capabilities impose limitations on the separation of true human signal from other species.…”
Section: Second Generation Sequencing Technologies (Sgsts) and Appmentioning
confidence: 99%
“…Samples were subjected to 40 cycles of denaturation (95oC, 30 sec), annealing (57°C, 30 sec) and extension (72oC, 60 sec). Capillary electrophoresis was performed and analyzed as described previously [21]. …”
Section: Methodsmentioning
confidence: 99%